3D Arrays for high throughput assay of cell migration and electrotaxis. (7th May 2013) - Zhao, Sanjun; Gao, Runchi; Devreotes, Peter N.; Mogilner, Alex; Zhao, Min
Abstract Cell behaviour in 3D environments can be significantly different from those in 2D cultures. With many different 3D matrices being developed and many experimental modalities used to modulate cell behaviour in 3D, it is necessary to develop high throughput techniques to study behaviour in 3D. We report on a 3D array on slide and have adapted this to our electrotaxis chamber, thereby offering a novel approach to quantify cellular responses to electric fields (EFs) in 3D conditions, in different matrices, with different strains of cells, under various field strengths. These developments used Dictyostelium cells to illustrate possible applications and limitations.